The Role of Labor Supervision (WASNAKER) In Resolving Legal Violations Regarding Wage Payment below the Minimum Wage - Gumilang, Iwan G.; Solichin, Solichin; Marlina, Tina; Ika Putri, Dessy; Aulia, Dhea Wardah (Jurnal Legisci, 2025)
Background, The annual rise in the nominal District/City Minimum Wage (UMK) is not accompanied by the adherence of Companies/Employers to fulfill their commitment to remunerate workers following the regulations. Labor Supervision, as the coordinator of oversight in the labor sector, encompasses coaching, inspection, testing, and investigation of labor offenses, playing a crucial role in addressing legal infractions related to the payment of wages below the District/City Minimum Wage (UMK). Aim, This study investigates the challenges encountered by Labor Supervision (WASNAKER) in addressing legal infractions concerning wage payments that fall below the district/city minimum wage (UMK). Methods, This article employs an empirical legal methodology utilizing a qualitative approach. Results, From this study, we found obstacles faced by the Cirebon Region III Manpower Supervision (WASNAKER) in handling legal violations against wage payments below the District/City Minimum Wage (UMK) by one of the Commanditaire Vennootschap (CV) in Cirebon Regency, including the Manpower Supervision which does not have executive power in carrying out its supervision activities and the absence of experts in the field of manpower who have certification at the Cirebon Region III Manpower Supervision. Conclusions, Efficient labor oversight is essential to guarantee the enforcement of regulations in compliance with the law. This oversight seeks to uphold labor standards via guidance, inspection, testing, and investigation of labor. However, in its implementation, supervision faces various obstacles, such as the lack of executive power in the supervision process and the absence of certified expert witnesses in the field of labor, as seen in Region III Cirebon. Implication, This study’s results highlight the importance of strengthening the oversight mechanism, including the provision of competent human resources, to ensure compliance with labor regulations and the protection of workers' rights.